DETERMINAN KETIMPANGAN PENDAPATAN MASYARAKAT DI DAERAH ISTIMEWA YOGYAKARTA - Tuti Nadhifah; Muhammad Ghafur Wibowo (Jurnal Ekonomi Dan Bisnis, 2021)
Income inequality is a problem related to income earned by people in an area between groups. The problem of inequality is very important to be studied, because it can affect the regional economy. This research was conducted with the aim of finding the factors that influence income inequality. This research is a descriptive study with a quantitative approach. The data in this study were 5 (five) provinces in the Special Region of Yogyakarta. The year period used is 2013-2019. This research method use Panel Data Regression. The results of this study indicate that the variables of economic growth and population do not have a positive and significant effect on income inequality. While the variable number of workers has a negative and significant effect on income inequality, besides that the hidden unemployment rate also has a positive and significant effect on income inequality. This research has implications for the theory of income inequality and the policies taken to deal with inequality by paying attention to the number of workers and the hidden unemployment rate in the Special Region of Yogyakarta for the period 2013-2019.